Réponses

Meilleure réponse !
2013-01-26T18:11:58+01:00

a) 4x+3y=4          4x + 3y = 4     multiplier par 3  12x + 9y = 12

    5y=6x+13       -6x + 5y = 13   multiplier par 2 -12x + 10y = 26 additionner 19y = 38

                                                                                                                           donc y = 2

si y = 2 : 4x + 6 = 4 => 4x = -2 => x = -1/2

 

a) 4x-6y=2                                     4x - 6y = 2

  -2x+7y=7 multiplier par 2 =>    -4x + 14y= 14 additionner 8y = 16 => y = 2

si y = 2 : -2x + 14 = 7 => -2x = -7 => x = 7/2